An Irshad-Based Approach in the Digital Age Through the Dhikr Practices of Habib Luthfi bin Yahya - Azkia, Yumna; Tawang, Nur Asia; Karadeniz, Vedat; Hasan, Moch Zainal Arifin; Sinawar, Sinawar (STAI Publisistik Thawalib Jakarta, 2025)
Habib Luthfi bin Yahya’s use of digital technology in disseminating dzikir has expanded the reach of Islamic preaching, created virtual spiritual communities, and strengthened religious interactions in an interactive and trustworthy manner. This study analyzes Habib Luthfi bin Yahya’s utilization of digital media to spread dzikir and provide spiritual guidance to the broader public engagingly and interactively. The research employs a qualitative approach and literature review, collecting data through documentation from various books, journals, and relevant online articles. The research findings indicate that da'wah in the digital era must adapt methods, content, and media to align with technological advancements and societal needs. The irsyad approach, which emphasizes personal relationships, effectively addresses psychological and spiritual issues. Dzikir therapy helps foster inner peace and closeness to God. Habib Luthfi bin Yahya serves as a model of a moderate scholar who wisely utilizes digital media to spread peaceful Islamic messages. Through online platforms, he builds spiritual communities and raises religious awareness across generations. This da'wah model combines Sufi values and Ahlussunnah wal Jamaah ethics, creating tolerant content and strengthening an inclusive Islamic identity. Conclusion: Digital technology is effective for Islamic preaching; scholars like Habib Luthfi spread Islam widely and profoundly through digital platforms.